Machine-apparatus scheme for the production of recombinant human insulin from E. coli inclusion bodies - Omelianenko, Kostiantyn; Kasyniuk, Maksym; Hrininh-Hera, Kateryna; Gubenia, Oleksii (My University, 2024)
The existing literature lacks a description of the machine-apparatus scheme for insulin production that is understandable for students of technical specialties. Data on the Internet are of poor quality and unfounded. Manufacturers' data are usually classified.
Keywords: інсулін; insulin; кафедра мехатроніки та пакувальної техніки; кафедра машин і апаратів харчових та фармацевтичних виробництв